Size-dependent stability of ultra-small α-/β-phase tin nanocrystals synthesized by microplasma - Atta Ul Haq (Nature Portfolio, 2019)
Key features of tin, including electronic band structure and opto-electronic properties, are influenced by the crystal structure. Here the authors report a microplasma process for the synthesis of ultra-small tin nanocrystals in which the crystal structure is dependent on crystallite size.